Mother-to-Child Transmission of Herpes Simplex Virus. (September 2014) - James, Scott H.; Sheffield, Jeanne S.; Kimberlin, David W.
Abstract: Infections with herpes simplex virus type 1 (HSV-1) or type 2 (HSV-2), both alpha herpesviruses, are highly prevalent worldwide. Both HSV types commonly cause genital infection, which, when acquired or reactivated during pregnancy, carries with it the risk of transmission to the fetus or neonate. Women who acquire primary or first-episode genital herpes during pregnancy are at greater risk for transmitting the infection than are women with recurrent genital herpes. Because viral infection and reactivation are frequently asymptomatic, many affected women are unaware of their infection and risk of transmission to their infants. Neonatal HSV infection can have devastating long-term consequences, especially when the central nervous system (CNS) is involved. Treatment of affected neonates with intravenous acyclovir has improved outcomes but there is room for further improvement, especially in regard to CNS disease. Working with pregnant women to prevent mother-to-child transmission of HSV is an important component in reducing the overall disease burden of neonatal HSV infections.